Answer:
x = -86
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define Equation
-26 = 60 + x
Step 2: Solve for x
- Subtract 60 on both sides: -86 = x
- Rewrite: x = -86
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: -26 = 60 - 86
- Subtract: -26 = -26
Here we see that -26 does indeed equal -26.
∴ x = -86 is the solution to the equation.